Folk culture in the digital age the emergent dynamic of human interaction - Blank, Trevor J. (Utah State University Press, an imprint of the University Press of Colorado, 2012)
Smart phones, tablets, Facebook, Twitter, and wireless Internet connections are the latest technologies to have become entrenched in our culture. Although traditionalists have argued that computer-mediated communication and cyberspace are incongruent with the study of folklore, Trevor J. Blank sees the digital world as fully capable of generating, transmitting, performing, and archiving vernacular culture. Folk Culture in the Digital Age documents the emergent cultural scenes and expressive folkloric communications made possible by digital "new media" technologies.